The Influence of Different Types of Outdoor Access on Dairy Cattle Behavior - Smid, Anne-Marieke C.; Weary, Daniel M.; von Keyserlingk, Marina A. G. (Frontiers in Veterinary Science, 2020)
Pasture access for dairy cows is highly valued both by cows and the public at large. When pasture access is not feasible, farmers can provide cows with alternative forms of outdoor access, such as an outdoor bedded pack, that may be easier to implement on some farms. We reviewed the literature on how feeding, lying, standing, walking, social and estrus behaviors are influenced by pasture and other types of outdoor areas. Pasture allows the expression of grazing and can facilitate the expression of lying, standing, walking and estrus behaviors. In addition, pasture can decrease the number of social interactions between cows, likely because more space per cow is provided than what is normally available indoors. The provision of soft flooring and an open space in outdoor bedded packs appears to provide some benefits for lying, standing and walking behavior and may also have positive effects on social behavior, especially with larger space allowances. The effects of an outdoor bedded pack on estrus behavior are less well documented, but the provision of a standing surface that provides better footing than typically available indoors may promote estrus behavior. Alternative outdoor areas assessed to date appear to be less attractive for cows than pasture, perhaps because these areas do not provide the opportunity to graze. We encourage future research to investigate the importance of grazing for dairy cows. The motivation of dairy cows to access alternative outdoor areas should also be investigated. As cow preference for the outdoors depends on many factors, providing cows a choice may be of particular importance.